Ant recolonisation of rehabilitated bauxite mines of Poços de Caldas, Brasil - Majer, Jonathan (1992)
The ant species were sampled in one campo (grassy shrubland), one mata (semideciduous rain forest) and 11 rehabilitated bauxite mine plots at Poços de Caldas, in the humid sub-tropical climatic region of Brazil. Rehabilitation was either by planting Australian Eucalyptus spp, the Brazilian Mimosa scabrella tree, or by planting mixed mata trees. Sixty-eight ant species were recorded, of which 26 were exclusively found in the native vegetation and 16 were confined to the rehabilitated plots. Ant species richness built up most rapidly in areas rehabilitated with mixed mata species and least rapidly in areas with Eucalyptus. Younger rehabilitated plots appeared to be developing a campo-type ant community, although evidence indicates that more mata ant species will colonise once tree canopy closure takes place. Rate of ant return in Australia is positively correlated with the quantity and distribution of rainfall – the rates in the current study concur with those from humid sub-tropical climatic zones within Australia, suggesting that similar constraints to the succession may be operating.